Factors influencing the acceptance of blockchain technology: real estate industry - Ng, Claudia; Lee, Angela Siew Hoong * (2021)
Blockchain is an innovative distributed ledger technology enabling the exchange of value online without the need of a central authority. Blockchain provides a decentralized and trustless network, secured by cryptography and consensus mechanisms. The acceptance of blockchain technology greatly impact the real estate owners, financiers, builders and more. Hence, this study attempts to find out how buyers and sellers of real estates are accepting blockchain technology by integrating and analysing a proposed hybrid model of UTAUT (Unified Theory of Acceptance and Use of Technology) combined with TRI (Technology Readiness Index). This study utilizes a quantitative research method and aims to identify the key influencing factors in the acceptance of blockchain technology. It is crucial to fully comprehend the potential of blockchain technology as it is a new revolutionary technology. This paper proposed a conceptual model that tests the performance expectancy, effort, social influence, facilitating condition, innovativeness, optimism, discomfort and insecurity in influencing the user intention behaviour in accepting blockchain technology. A pilot-test was conducted to test the research model. The results showed that all composite reliability values except for ‘Social Influence’ were found to be above the recommended value of 0.70, suggesting strong indicator reliability of the constructs.